AUTOMATIC CONTROL OF LIGHTING - Babenko, Olexiy; Gaiday, Andriy; Zakharchuk, Olexandre (Scientific Works of Vinnytsia National Technical University, 2015)
The system of automatic control of artificial lighting has been developed, the system provides colour temperature and brightness of lighting, close to solar light in real time. REFERENCES 1. Шуберт Ф. Светодиоды / Ф. Шуберт. – М.: ФИЗМАТЛИТ, 2008. – 496 с. 2. Light’s Labours Lost – Fact Sheet // Intenational energy agency [Електронний ресурс]. – Режим доступу: http://www.iea.org/publications/freepublications/publication/light_fact.pdf . 3. ATmega16 – User Guide / Atmel Corporation [Електронний ресурс]. – Режим доступу: http://www.atmel.com/Images/doc2466.pdf. 4. Four Great Reasons to Dim – Lutron Electronics [Електронний ресурс]. – Режим доступу: http://europe.lutron.com/dim.htm. 5. Андреев С. П. ИК – пассивные датчики охранной сигнализации / С. П. Андреев // Специальная техника. – 1998. – № 1. – С. 20 – 30.